Role of the Specialized Proresolving Mediator Resolvin D1 in Systemic Lupus Erythematosus: Preliminary Results. (21st October 2018) - Navarini, Luca; Bisogno, Tiziana; Margiotta, Domenico Paolo Emanuele; Piccoli, Alessandra; Angeletti, Silvia; Laudisio, Alice; Ciccozzi, Massimo; Afeltra, Antonella; Maccarrone, Mauro
Abstract : Objective . Systemic lupus erythematosus (SLE) is an autoimmune systemic disease and its pathogenesis has not yet been completely clarified. Patients with SLE show a deranged lipid metabolism, which can contribute to the immunopathogenesis of the disease and to the accelerated atherosclerosis. Resolvin D1 (RvD1), a product of the metabolism of the omega-3 polyunsaturated fatty acid docosahexaenoic acid (DHA), acts as a specialized proresolving mediator which can contribute in restoring the homeostasis in inflamed tissues. The aim of the present pilot study is to evaluate plasma levels of RvD1 in patients with SLE and healthy subjects, investigating its potential role as a biomarker of SLE and assessing its relationship with disease activity and laboratory parameters. Methods . Thirty patients with SLE and thirty age- and sex-matched healthy subjects (HSs) have been consecutively recruited at Campus Bio-Medico University Hospital. RvD1 plasma levels were measured by ELISA according to the manufacturer's protocol (Cayman Chemical Co.). RvD1 levels were compared using Mann–Whitney test. Discriminatory ability for SLE has been evaluated by the area under the ROC curve. Results . Lower levels of RvD1, 45.6 (35.5–57.4) pg/ml, in patients with SLE have been found compared to HSs, 65.1 (39.43–87.95) pg/ml (p = 0.0043 ). The area under the ROC curve (AUC) for RvD1 was 0.71 (95% CI: 0.578–0.82) and the threshold value of RvD1 for the classification of SLE was <58.4 pg/ml, sensitivity 80% (95% CI: 61.4–92.3), and specificity 63.3% (95% CI: 43.9–80.1), likelihood ratio 2.2 (95% CI: 1.3–3.6). Conclusions . The present preliminary study allows hypothesizing a dysregulation of RvD1 in patients with SLE, confirming the emerging role of bioactive lipids in this disease.